The Eighth Graders' Higher Order Thinking Skills in Solving Numeracy Problems-Based Minimum Competency Assessment - Meryansumayeka Meryansumayeka; Muhammad Yusuf; Scristia Scristia; Kamaliyah Kamaliyah (Universitas Maritim Raja Ali Haji, 2022)
The Indonesian government makes efforts to improve students' higher-order thinking skills by implementing a Minimum Competency Assessment or Assessment Kompetensi Minimum (AKM) as a substitute for the National Examination. With the implementation of the AKM, it is necessary to find out how students can solve these questions. This research analyzed students' higher-order thinking skills in solving AKM-type math problems. The research method used is descriptive qualitative research consisting of 3 stages: the preparation stage, the implementation stage, and the data analysis stage. The research was conducted in the odd semester of the 2020/2021 academic year with the research subjects of eleven 8th grade students of SMP IT Raudhatul Ulum Sakatiga, South Sumatra, and SMPN 11 Banjarbaru, South Kalimantan. Data collection techniques used are tests, documentation, observation, and interviews. The data were analyzed qualitatively. The results showed that students with high abilities could solve several questions that required analytical power but were still weak in solving questions that required evaluation. Other students still need to improve their analytical and evaluation skills.